ЕТИЧНИЙ БРЕНДИНГ ЯК СТРАТЕГІЯ СТАЛОГО ЗРОСТАННЯ НА ГАЛУЗЕВИХ РИНКАХ - Plysenko, Halyna (Zhytomyr Ivan Franko State University, 2025)
The article considers the market-oriented nature of ethical branding within the context of the transformation of the global business environment. The relevance of the study is substantiated by the growing need to adapt traditional branding strategies to the conditions of sustainable development, increased social responsibility, and heightened environmental awareness. The purpose of the research is to examine the role of ethical practices in shaping a sustainable brand and their impact on a company's competitiveness and long-term success. Examples of well-known ethical brands (Dove, Patagonia, IKEA) that integrate the values of transparency, social justice, and environmental responsibility into all business processes are analyzed. It is revealed that sustainability in branding encompasses not only the environmental dimension but also the social one particularly fair marketing positioning, ethical labor relations, and support for local communities. Ethical branding is not merely a strategy for external communication, but a comprehensive business philosophy that encompasses all stages from raw material sourcing to product disposal. Rooted in principles of responsibility and transparency, this philosophy becomes a powerful tool for enhancing a company’s reputational capital. Special attention is paid to the Ukrainian context, where an increasing number of fashion industry brands (Bevolex, Bettter, Armchairity) are implementing ethical principles and shaping a new culture of business ethics. It is emphasized that for an ethical brand, not only declared values matter but also real actions: from rejecting harmful practices to taking a clear social stance, including ending cooperation with the aggressor country. As a result of the study, it is concluded that ethical branding not only builds consumer trust and a positive image but also enhances economic efficiency, attracts investment, motivates employees, and ensures the long-term resilience of a business. It is substantiated that ethical branding is a strategic necessity rather than a passing trend and it will define the standards of responsible entrepreneurship in the future.